Possibilities of predicting purulent-inflammatory complications after cesarean section - I. I. Kutsenko; I. O. Borovikov; M. V. Galustyan; A. S. Magay; O. I. Borovikova (Медицинский вестник Юга России, 2023)
Objective: identify the main risk factors in the development of purulent-inflammatory complications after cesarean section. Materials and methods: puerperal women after cesarean section (n = 90): 24 patients with a complication of puerperia in the form of endometritis (group I), 16 — with the insolvency of the suture on the uterus (group II) and 50 — with a physiologically occurring postoperative period (group (III) of control). An analysis of anamnestic, clinical and laboratory studies of puerperal women after abdominal delivery with a complicated postoperative period was carried out. With the help of logistic regression with the construction of an ROC-curve, a rank correlation analysis of the influence of adverse factors with the calculation of diagnostic coefficients (DC) was performed. Results: based on the assessment of the identified main clinical-anamnestic and laboratory predictors, using mathematical modeling methods, a scale for predicting the risk of purulent-inflammatory complications in early puerperia after abdominal delivery has been developed. Conclusion: prognostic mathematical scale for assessing the risk of purulent-inflammatory complications in puerperal women after abdominal delivery makes it possible to identify the main predictors of infectious diseases in these patients, which contributes to their timely prevention and, thereby, reducing the frequency of severe forms of postpartum infection.